The complete mitochondrial genome of the Antarctic fairy shrimp Branchinecta gaini Daday, 1910 (Branchiopoda, Anostraca, Branchinectidae) - Jo, Euna; Kim, Jin-Hyoung; Ko, Young Wook; Kim, Sanghee; Kang, Seunghyun (Pensoft Publishers, 2022)
The complete mitochondrial genome of Antarctic fairy shrimp Branchinecta gaini Daday, 1910 was sequenced, assembled and annotated using next-generation sequencing technology. The mitogenome of B. gaini is circular at 15,536 bp in length, consisting of 13 protein-coding genes, 23 tRNAs, two rRNAs and two major non-coding regions. In particular, there are two tRNA Gly genes and one non-coding region between these two tRNA Gly genes. A phylogenetic tree was constructed using concatenated amino acid sequences of 13 protein-coding genes. It reveals that B. gaini is clustered with the Anostraca group within the Branchiopoda clade. This study helps us understand the evolution of Anostraca.